PREFERENCE OF ENGLISH LANGUAGE TEACHING METHODS AND TECHNIQUES OF PROSPECTIVE TEACHERS IN KONGUMANDALAM REGION - Barathi, C.; Naveen, A. (International Journal of Research -GRANTHAALAYAH, 2017)
The present study is made on “Preference of English language teaching methods and techniques of prospective teachers in Kongumandalam Region”. A sample of 847 prospective teachers from 41 B.Ed colleges in Kongumandalam region who were studying English pedagogy as main subject has been selected based on simple random sampling technique. This will constitute 71.65 (847/1182) percentage of sample from the total population. A normative research method and survey technique has been adopted. The descriptive statistical analysis shows that the prospective teachers belonging to Coimbatore district had higher preference of English language teaching methods and techniques, and high personality traits and Nilgiris district had high styles of learning and thinking. The level of preference of English teaching methods and techniques, personality traits and style of learning and thinking of prospective teachers was average for the whole sample and sub-sample. The regression statistical analysis had shown that daily newspaper reading, personality traits and speaking in English were the strong predictors of preference of English language teaching methods and techniques of prospective teachers in the Kongumandalam region.